Effect of Strategic Alignment on Performance of Non-Governmental Organizations in Northern Region of Kenya - Amoni, Thomas; Atandi, Gichana; Okwemba, Emily (International Journal of Strategic Management, 2025)
Purpose: This study investigates the impact of strategic alignment and the performance of NGOs specifically within the dimensions of strategic thinking, goal consistency, resource allocation, and communication on the overall effectiveness of NGOs operating in Northern Kenya. Methodology: Adopting a pragmatist philosophy, the research employs a mixed-methods, cross-sectional design to explore these dynamics comprehensively. Quantitative data were collected through structured questionnaires from 166 NGO leaders across seven counties, representing a response rate of 70.9%, with high internal consistency (Cronbach’s alpha ranging from 0.793 to 0.891). The questionnaires measured variables including strategic thinking, strategic alignment, performance of NGOs, and other relevant factors. Descriptive statistics indicated strong agreement on the influence of strategic alignment on decision-making and innovation facilitation. Qualitative insights from 15 key informant interviews, focus groups, and document analysis provided contextual understanding of adaptive leadership practices and cultural challenges. Data analysis involved correlation, regression, and structural equation modeling (SEM) using SPSS and AMOS, with SEM explaining 67.2% of variance in NGO performance (R² = 0.672). Ethical protocols ensured participant confidentiality and cultural sensitivity throughout the research process. Findings: Correlation analysis revealed a significant positive relationship between strategic alignment and NGO performance (r = 0.598, p < 0.01). Regression results confirmed that strategic alignment explains 40.3% of performance variability, with dimensions such as goal consistency, resource allocation, and communication all contributing significantly resource allocation being the most influential (β = 0.312, p < 0.001). The SEM further established that strategic alignment, combined with competence management and other factors, strongly predicts NGO performance, with cultural factors moderating these effects. Qualitative themes highlighted the importance of adaptive leadership, stakeholder engagement, and capacity building, aligning with quantitative findings and emphasizing the critical role of cultural and contextual factors in strategic effectiveness. Unique Contribution to Theory, Practice and Policy: This research contributes to strategic alignment theory by emphasizing the necessity of contextually adaptive practices in resource-limited, culturally diverse environments like Northern Kenya. It demonstrates that strategic alignment particularly through goal coherence, resource management, and effective communication significantly enhances NGO performance. The findings advocate for capacity building in strategic thinking and organizational practices to foster innovation, flexibility, and stakeholder engagement, which are essential for sustaining NGO effectiveness in complex operational landscapes.